Economic elasticity and linguistic strategies in marketing processed Cassava: A systematic literature review - Sony Tian Dhora; Asriani Abbas; Defrizal Defrizal; Vonny Tiara Narundana; Dian Resha Agustina (Journal of Economics Research and Policy Studies, 2025)
The processed cassava industry in Indonesia plays a strategic role in supporting food security and regional economic development, yet it remains underexplored from the perspectives of economic elasticity and promotional language. This systematic literature review synthesizes recent empirical and theoretical studies on price and income elasticity and linguistic strategies in agro-food marketing. Literature searches were conducted using the Publish or Perish 8 software across Scopus, Web of Science, and Google Scholar databases for the 2019–2025 period with the keywords “cassava industry,” “price elasticity,” “income elasticity,” “marketing discourse,” and “linguistic strategy in agro-food.” From an initial 200 articles, 43 met the inclusion criteria and were analyzed in depth. The findings reveal that the price elasticity of processed cassava products varies across market segments, influenced by product differentiation and consumer income. Promotional language employing metaphors, health claims, and cultural references enhances consumer perception and willingness to pay. This study highlights the importance of integrating economic elasticity analysis with discourse-based marketing strategies to strengthen competitiveness and sustainability in Indonesia’s processed cassava industry.